Exam Experiences, Motivational Beliefs, and Belonging in First-Year University Physics Students: Insights from the COVID-19 Pandemic (Teaching and Learning Inquiry, 2024)
The COVID-19 pandemic provided an opportunity to better understand the transition from secondary school to higher education regarding students’ assessment and written-exam experiences. We used mixed methods to investigate students’ experiences of first-year university physics exams and cancelled secondary school exams, regarding their motivational beliefs (regarding themes such as self-efficacy and test anxiety) and sense of belonging. Questionnaire findings from 78 physics students suggest those who felt more negatively impacted by cancelled school exams felt less prepared, less self-efficacious, and more anxious in their university exams than students who felt more positively impacted. Follow-up focus groups with five students revealed they felt out of practice sitting high-stakes university exams and unprepared for the new open-book format, contributing to their test anxiety. Cancelled school exams also provided short-term relief, but belongingness uncertainty; students felt unable to prove themselves and questioned whether they had earned their place in higher education. Our findings suggest that the exam experience is central to both creating a sense of belonging for students and building mastery experiences in terms of self-efficacy and test anxiety.